Designing Authentic Science Assessment for Pre-Service Science Teachers - Mustafa Tüysüz; Ümmüye Nur Tüzün; Hayati Çavuş (Dinamika Ilmu, 2023)
The current research aimed to design an authentic science assessment domain for pre-service science teachers to enhance their higher thinking skills, such as critical thinking skills, being aware that if pre-service science teachers experienced effective authentic assessment domains, they would be much more skillful in their future classes. The research was conducted with the case study as one of the qualitative research designs. The authentic assessment process was performed on Cunningham engineering design integrated with Toulmin argument pattern components. Worksheets were utilized as data-collecting devices for the authentic science assessment process. Descriptions and content analysis were used for the evaluation of the gathered data. At the end of the study, it illustrated an innovative application of an authentic science assessment for pre-service science teachers in detail. Such a creative authentic science assessment process based on Cunningham engineering design integrated with Toulmin argument pattern components made pre-service science teachers construct their argument so as to think critically. Also, the illustrated authentic assessment domain would be a multicultural guide for university educators. In the current research, only an authentic science assessment domain was illustrated, this was the limitation of the research, so for further studies, authentic assessment domain constructions could be suggested.